PRaG 3.0 therapy for human epidermal growth factor receptor 2-positive metastatic pancreatic ductal adenocarcinoma: A case report - Kong, Yue-Hong; Xu, Mei-Ling; Zhang, Jun-Jun; Chen, Guang-Qiang; Hong, Zhi-Hui; Zhang, Hong; Dai, Xiao-Xiao; Ma, Yi-Fu; Zhao, Xiang-Rong; Zhang, Chen-Yang; Chen, Rong-Zheng; Xing, Peng-Fei; et al. (World journal of gastroenterology : WJG, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is a highly fatal disease with limited effective treatment especially after first-line chemotherapy. The human epidermal growth factor receptor 2 (HER-2) immunohistochemistry (IHC) positive is associated with more aggressive clinical behavior and shorter overall survival in PDAC. We present a case of multiple metastatic PDAC with IHC mismatch repair proficient but HER-2 IHC weakly positive at diagnosis that didn't have tumor regression after first-line nab-paclitaxel plus gemcitabine and PD-1 inhibitor treatment. A novel combination therapy PRaG 3.0 of RC48 (HER2-antibody-drug conjugate), radiotherapy, PD-1 inhibitor, granulocyte-macrophage colony-stimulating factor and interleukin-2 was then applied as second-line therapy and the patient had confirmed good partial response with progress-free-survival of 6.5 months and overall survival of 14.2 month. She had not developed any grade 2 or above treatment-related adverse events at any point. Percentage of peripheral CD8 Temra and CD4 Temra were increased during first two activation cycles of PRaG 3.0 treatment containing radiotherapy but deceased to the baseline during the maintenance cycles containing no radiotherapy. PRaG 3.0 might be a novel strategy for HER2-positive metastatic PDAC patients who failed from previous first-line approach and even PD-1 immunotherapy but needs more data in prospective trials.